Extended-GS optimum solution for multi-criteria and multi-alternative problem. (8th June 2023) - Abu-Taieh, Evon; Al-Rasheed, Amal; Alohali, Manal
Decisions in this competitive and dynamic world must be correct, accurate, and objective. The process of deciding must be fast and precise. Since the dawn of technology, criteria and alternatives increased. Hence, tools, techniques, and methods were developed to conduct the process of decision making swiftly and correctly. Multi-criteria decision-making (MCDM) enhances the decision-making process by relying on calculated decisions rather than guessed decisions. Further, solving tools and techniques are perforated with gaps. To bridge such gaps between the tools and techniques, this paper suggests, extended version of Gale-Shapley (E-GS) algorithm that utilises three MCDM methods: analytic hierarchy process (AHP), weighted product model (WPM), and weighted sum model (WSM). The basic idea of the E-GS algorithm is feeding the preference lists required by the Gale-Shapley algorithm to produce an optimum match using WSM, WPM, and AHP models. E-GS combined the powers of all four algorithms to provide an optimum solution.